Biochemical Properties of Human D-Amino Acid Oxidase - Murtas, Giulia; Sacchi, Silvia; Valentino, Mattia; Pollegioni, Loredano (Frontiers in Molecular Biosciences, 2017)
D-amino acid oxidase catalyzes the oxidative deamination of D-amino acids. In the brain, the NMDA receptor coagonist D-serine has been proposed as its physiological substrate. In order to shed light on the mechanisms regulating D-serine concentration at the cellular level, we biochemically characterized human DAAO (hDAAO) in greater depth. In addition to clarify the physical-chemical properties of the enzyme, we demonstrated that divalent ions and nucleotides do not affect flavoenzyme function. Moreover, the definition of hDAAO substrate specificity demonstrated that D-cysteine is the best substrate, which made it possible to propose it as a putative physiological substrate in selected tissues. Indeed, the flavoenzyme shows a preference for hydrophobic amino acids, some of which are molecules relevant in neurotransmission, i.e., D-kynurenine, D-DOPA, and D-tryptophan. hDAAO shows a very low affinity for the flavin cofactor. The apoprotein form exists in solution in equilibrium between two alternative conformations: the one at higher affinity for FAD is favored in the presence of an active site ligand. This may represent a mechanism to finely modulate hDAAO activity by substrate/inhibitor presence. Taken together, the peculiar properties of hDAAO seem to have evolved in order to use this flavoenzyme in different tissues to meet different physiological needs related to D-amino acids.